Effects of increasing levels of lasalocid supplementation on growth performance, serum biochemistry, ruminal fermentation profile, in vitro nutrient digestibility, and gas production of growing goats - Basmaeil, Saeid M.; Suliman, Gamaleldin M.; Al Garadi, Maged A.; Al-Badwi, Mohammed A.; Abdelrahman, Mutassim M.; Al-Harbi, Fahad S.; El-Waziry, Ahmed M.; Alhidary, Ibrahim A.; Swelum, Ayman A. (Frontiers in Veterinary Science, 2023)
Lasalocid is a feed additive widely used in ruminant nutrition and plays a crucial role in improving livestock productivity, digestibility, immunity, and overall well-being. The current study was conducted to investigate the effect of different levels of Lasalocid (LAS) supplementation on growth performance, serum biochemistry, ruminal fermentation profile and in vitro nutrient digestibility and gas production of growing goats. A total of 60 growing Aardi male goats with averaging body weight of ~17.12 kg (3-month-old) were used for an 84-day trial. Animals were randomly divided into four treatments with 5 replicates of 3 goats each. All four groups were provided with a basal diet supplemented with Lasalocid (LAS) at 0 (without supplementation; LAS0), 10 (LAS10), 20 (LAS20), or 30 (LAS30) ppm LAS /kg dry matter (DM). Feed intake was measured weekly, and goats were weighed every two weeks for an evaluation of the performance parameters. Blood samples were collected for the measurement of biochemical variables. In vitro nutrient digestibility and gas production, were evaluated. The supplementation of LAS at level 30 ppm /kg DM increased (P < 0.05) body weight gain and average daily gain without linear or quadratic effect. The serum concentrations of high-density lipoprotein were significantly (p < 0.05) higher in the LAS20 group than in other groups with linear and quadratic effects. While, low-density lipoprotein concentration was significantly lower in the LAS20 group than in LAS0 and LAS30 with a linear effect. Different levels of Lasalocid supplementation had no effect on the ruminal fermentation profile and in vitro gas production and nutrient digestibility. In conclusion, the addition of LAS (20~30 ppm /kg DM) to the goat’s diet can improve the growth performance and lipoprotein profile.